The Ethics of Meaningful Work: Types and Magnitude of Job-Related Harm and the Ethical Decision-Making Process - May, Douglas R.; Li, Cuifang; Mencl, Jennifer; Huang, Ching-Chu (Journal of business ethics, 2014)
This research on the ethics of meaningful work examined how types of job-related harm (physical, economic, emotional, and cognitive) and their magnitude of consequences (MOC, low, high) influenced components of ethical decision-making (moral recognition, moral evaluations, and moral intentions). The research also investigated the moderating effects of individual differences (experience with carpal tunnel syndrome, experience with layoffs, ability to read others' emotions, and intrinsic motivation orientation [IMO]) on the relation between the MOC and the ethical decision-making elements for each type of harm. Using a sample of 185 Chinese professionals, a between-subjects, fully crossed experimental scenario design revealed that physical and economic job-related harm were recognized as moral issues to a greater extent than cognitive or emotional harm. Second, physical job-related harm stimulated a higher level of moral evaluations than economic and cognitive harm. Third, individuals intended to act ethically when MOC was high versus low. Finally, experience with layoffs and IMO helped explain the relations between MOC and moral evaluations for economic and cognitive job-related harm, respectively. Implications for research and management are discussed.